Liriope muscari ’Evergreen Giant’ Evergreen Giant Lilyturf: FPS-348/FP348, 5/2007 - Gilman, Edward (EDIS, 2007)
This document provides an overview of the Evergreen Giant Liriope (Liriope muscari ‘Evergreen Giant’), a perennial, herbaceous ornamental grass. It highlights its attractive dark green foliage and lilac purple blooms, making it a popular groundcover. The plant thrives in USDA hardiness zones 6 through 10 and can be planted year-round in zones 7 to 10. It is noted for its moderate growth rate, fine texture, and ability to grow in part shade or full shade. The document also discusses its soil tolerances, moderate drought tolerance, and minimal care requirements, making it a versatile and low-maintenance option for various landscaping uses. Original publication date October 1999.